Justice Connect Project - Garvin Eric Jjuuko; Crystal Nimaro-Kilibo; Abigail Agnes Mulungi; Suzan Karunga (Uganda Christian University, 2024)
J-Connect is a web application designed to address the pressing issue of domestic violence in our society Mukono, Uganda. The platform aims to empower victims of domestic violence by providing them with convenient and affordable access to legal support. Specifically tailored to the needs of those affected by domestic abuse, J-Connect serves as a vital link between victims, particularly women, and qualified legal professionals in the country. Through our innovative consultation platform, users can easily seek advice from lawyers anonymously offering both pro bono and commercial legal aid support. Moreover, J-Connect goes beyond consultation by enabling users to select representation through a user-friendly interface, thereby promoting access to justice and advancing the objectives of SDG 16. J-Connect, is committed to fostering a safer and more equitable society for all fighting the stigmatization the victims face.